"Will It Rain?" Activities Investigating Aerosol Hygroscopicity and Deliquescence - Caetano-Silva, L. [UNESP]; Allen, Andrew George [UNESP]; Campos, Maria Lúcia Arruda de Moura; Cardoso, Arnaldo Alves [UNESP] (American Chemical Society (ACS), 2014)
Climate change and its consequences seem to be increasingly evident in our daily lives. However, is it possible for students to identify a relationship between these large-scale events and the chemistry taught in the classroom? The aim of the present work is to demonstrate that chemistry can assist in elucidating important environmental issues. Simple experiments are used to demonstrate the mechanism of cloud formation, as well as the influence of anthropogenic and natural emissions on the precipitation process. The experiments presented show the way in which particles of soluble salts commonly found in the environment can absorb water in the atmosphere and influence cloud formation.
Keywords: High School/Introductory Chemistry; Environmental Chemistry; Hands-On Learning/Manipulatives; Atmospheric Chemistry